Transforming gender norms and empowering women in livestock farming - Nguyen Thi Kieu Trang; Nguyen Thi Minh Phuong; Truong Thuy Hang; Galie, Alessandra; Pazos, Mateo; Duong Kim Anh; Triana Angel, Natalia (International Livestock Research Institute, 2024)
In September and October 2024, the CGIAR Initiative on Sustainable Animal Productivity (SAPLING, 2022–2024) kicked off a communication campaign focused on gender in Mai Son District, Son La Province, in the northwest highlands of Vietnam. This animation video was produced by SAPLING to share the key messages from baseline studies exploring gender norms and women's empowerment in livestock farming.